Thermodynamics of fluids under flow - Jou, D. (David); Casas-Vázquez, J. (José) 1938-; Criado-Sancho, M. (Manuel) 1948- (Dordrecht, Netherlands Springer Dordrecht, 2010)
This is the second edition of the book "Thermodynamics of Fluids under Flow," which was published in 2000 and has now been corrected, expanded and updated. This is a companion book to our other title Extended irreversible thermodynamics (D. Jou, J. Casas-Vazquez and G. Lebon, Springer, 4th edition 2010), and of the textbook Understanding non-equilibrium thermodynamics (G. Lebon, D. Jou and J. Casas-Vazquez, Springer, 2008. The present book is more specialized than its counterpart, as it focuses its attention on the non-equilibrium thermodynamics of flowing fluids, incorporating non-t
Non-equilibrium thermodynamics and rheology -- Non-equilibrium temperature and entropy in flowing ideal gases: maximum-entropy approach -- Kinetic theory of flowing gases and phonons, phonon hydrodynamics and heat transport in nanosystems -- Non-ideal fluids and nuclear collisions -- Polymeric solutions and blends -- Non-equilibrium chemical potential and shear-induced effects in polymer solutions and blends -- Comparison of thermodynamical and dynamical approaches -- Shear-induced migration and flow chromatography -- Taylor dispersion and anomalous diffusion -- Chemical reactions and polymer degradation under flow -- Non-equilibrium thermodynamics of laminar and turbulent superfluids
Electronic reproduction.
Keywords: Nonequilibrium thermodynamics; Fluid mechanics; Science; Physics